2011
DOI: 10.3109/02713683.2011.623810
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tear Osmolarity in Patients with Severe Cases of Conjunctivochalasis

Abstract: Hyperosmolarity of tear was reported as a fact of ocular surface inflammation. While in mild and moderate conjunctivochalasis tear osmolarity was similar to normal controls, increased osmolarity can refer to the presence of ocular surface inflammation in these patients with severe conjunctivochalasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…But in mild and moderate cases HLA-DR expression was similar to normal controls. In another study of Fodor et al15 the authors reported that tear osmolarity is elevated in only severe CCh; in mild and moderate cases, tear osmolarity was similar to normal controls. Zhang et al16 compared tear protein between CCh and normal controls.…”
Section: Discussionmentioning
confidence: 87%
“…But in mild and moderate cases HLA-DR expression was similar to normal controls. In another study of Fodor et al15 the authors reported that tear osmolarity is elevated in only severe CCh; in mild and moderate cases, tear osmolarity was similar to normal controls. Zhang et al16 compared tear protein between CCh and normal controls.…”
Section: Discussionmentioning
confidence: 87%
“…However, we found low levels of HLA‐DR expression compared to those found in KCS or secondary to drugs with preservative; this is probably why osmolarity was not increased in our series. A change in tear osmolarity probably requires substantial disturbance of the ocular surface (Fodor et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…36 Severe cases have been linked to increased tear osmolarity and inflammatory markers, which are often associated with dry eye states. 37,38 Le and colleagues 39 have recently demonstrated that patients with conjunctivochalasis have significantly decreased tear film stability even compared with those with DED and have significantly higher Ocular Surface Disease Index (OSDI) scores than do normal controls.…”
Section: Conjunctival Excision and Cauterymentioning
confidence: 98%